2018
DOI: 10.1108/add-07-2017-0008
|View full text |Cite
|
Sign up to set email alerts
|

Novel psychoactive substance use by mental health service consumers: an online survey of inpatient health professionals’ views and experiences

Abstract: Purpose: There is evidence that novel psychoactive substances (NPS) are commonly used by people with severe mental illness. The aim of the study was to undertake a scoping survey to explore inpatient mental health workers' perceptions of NPS use by consumers.Design/methodology: A cross-sectional online survey of mental health professionals.Participants were opportunistically recruited through social media and professional networks.Findings: A total of 98 participants (of 175 who started the survey) were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Previously, Schifano et al [53] stressed the need for HCPs to be continuously updated with regards to the constantly changing drug scenarios to identify new, emerging trends that can help with the provision of immediate interventions. Results (Figure 4) suggested improvements where self-reported levels of knowledge on NPS were mostly 'basic' (n = 76; 39.2%) and 'intermediate' (n = 73; 37.6%), which is in contrast to other studies that have reported inadequate HCP knowledge [40][41][42]. Nurses and pharmacists, predominantly working in hospitals and substance misuse services, had the most encounters with NPS use.…”
Section: Characteristics Of Hcpsmentioning
confidence: 81%
See 1 more Smart Citation
“…Previously, Schifano et al [53] stressed the need for HCPs to be continuously updated with regards to the constantly changing drug scenarios to identify new, emerging trends that can help with the provision of immediate interventions. Results (Figure 4) suggested improvements where self-reported levels of knowledge on NPS were mostly 'basic' (n = 76; 39.2%) and 'intermediate' (n = 73; 37.6%), which is in contrast to other studies that have reported inadequate HCP knowledge [40][41][42]. Nurses and pharmacists, predominantly working in hospitals and substance misuse services, had the most encounters with NPS use.…”
Section: Characteristics Of Hcpsmentioning
confidence: 81%
“…Previous studies have addressed the inadequacy in essential knowledge and skills required by HCPs on NPS to inform various interventions and highlighted the need for education on these novel molecules [38][39][40][41][42][43]. However, several studies only focused on specific professions and geographical locations in the UK [40][41][42][43]. The deficit in general knowledge on NPS may lead to inappropriate medical diagnoses and potentially the provision of inappropriate medical advice or interventions.…”
Section: Studies Exploring Nps Knowledge Among Healthcare Professionamentioning
confidence: 99%
“…The only intervention study aiming to reduce these errors found that a new medication dispensing system did not have any significant impact on patient safety 353. Two studies explored staff perceptions of illicit substance use 354 355. One further study described the development of a medication adherence intervention for patients who are prescribed mood-stabilising medication for bipolar disorder 356…”
Section: Resultsmentioning
confidence: 99%
“…Despite the Department of Health publishing specific guidance on screening and assessment for inpatient services, this is not common practice (Hughes et al, 2012). This may be in part due to the lack of substance misuse training for staff, and staff consequently lacking the skills and confidence needed (Hughes et al, 2019). There have been numerous calls for training on drug and alcohol use to be provided to staff working in PICUs so comorbid substance misuse can be detected, managed and addressed during treatment (Barnaby, 2003;Place et al, 2017;Hughes et al, 2012).…”
Section: The Impact Of Substance Misuse On Psychiatric Intensive Care Unitsmentioning
confidence: 99%